2014
DOI: 10.2146/ajhp130674
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of bariatric surgery patients

Abstract: The management of patients in the perioperative period of bariatric surgery requires appropriate selection and dosing of medications for pain management and treatment of infectious complications, VTE, bleeding, and other chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 78 publications
0
6
0
2
Order By: Relevance
“…For patients continuing use of antidiabetic and antihypertensive agents after discharge, pharmacists should provide education about the importance of monitoring for signs and symptoms of hypoglycemia and hypotension, and should recommend further dose reductions or discontinuation of medications as appropriate. 60 Interventions to reduce obesity are important to combat this epidemic in developed countries, especially in the location of this study, Newfoundland and Labrador, where 27.7% of residents are classified as obese, with a projected increase to 34.6% by 2019. 24,61 Sleeve gastrectomy offers an effective alternative to Roux-en-Y gastric bypass.…”
Section: Discussionmentioning
confidence: 95%
“…For patients continuing use of antidiabetic and antihypertensive agents after discharge, pharmacists should provide education about the importance of monitoring for signs and symptoms of hypoglycemia and hypotension, and should recommend further dose reductions or discontinuation of medications as appropriate. 60 Interventions to reduce obesity are important to combat this epidemic in developed countries, especially in the location of this study, Newfoundland and Labrador, where 27.7% of residents are classified as obese, with a projected increase to 34.6% by 2019. 24,61 Sleeve gastrectomy offers an effective alternative to Roux-en-Y gastric bypass.…”
Section: Discussionmentioning
confidence: 95%
“…Changes in drug absorption after bariatric surgery as well as evolving hormonal alterations must be considered. 207,208 An integrated approach, including collaborative multidisciplinary care that modifies surgical methods and uses additional pain management tools, can decrease the requirement for opioids and encourage rehabilitation. 181,209,210 Concerning reports indicate that some patients (13%) suffer from worsened depression after bariatric surgery.…”
Section: Interventional Pain Management In Obese Patientsmentioning
confidence: 99%
“…A detailed review of acute perioperative concerns in the bariatric surgery patient can be found in a separate publication. 2…”
Section: Discussionmentioning
confidence: 99%